2010
DOI: 10.1186/2041-9414-1-7
|View full text |Cite
|
Sign up to set email alerts
|

UHRF1 is a genome caretaker that facilitates the DNA damage response to γ-irradiation

Abstract: BackgroundDNA double-strand breaks (DSBs) caused by ionizing radiation or by the stalling of DNA replication forks are among the most deleterious forms of DNA damage. The ability of cells to recognize and repair DSBs requires post-translational modifications to histones and other proteins that facilitate access to lesions in compacted chromatin, however our understanding of these processes remains incomplete. UHRF1 is an E3 ubiquitin ligase that has previously been linked to events that regulate chromatin remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 43 publications
(69 reference statements)
3
32
0
Order By: Relevance
“…As shown in Fig. 1A, we found that the UHRF1 protein level is also regulated in response to DNA damage, i.e., the UHRF1 protein level is reduced upon UV irradiation, consistent with a proposed role of UHRF1 in the DDR (16,20,(25)(26)(27). The reduction of UHRF1 in the DDR is likely attributable to proteasome-mediated degradation, because the proteasome inhibitor MG132 restored Interestingly, the USP7 level and its interaction with UHRF1 remained unaltered in the DDR (Fig.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…As shown in Fig. 1A, we found that the UHRF1 protein level is also regulated in response to DNA damage, i.e., the UHRF1 protein level is reduced upon UV irradiation, consistent with a proposed role of UHRF1 in the DDR (16,20,(25)(26)(27). The reduction of UHRF1 in the DDR is likely attributable to proteasome-mediated degradation, because the proteasome inhibitor MG132 restored Interestingly, the USP7 level and its interaction with UHRF1 remained unaltered in the DDR (Fig.…”
Section: Resultssupporting
confidence: 60%
“…Similarly, knockdown of UHRF1 in HEK293 and WI-38 cells also renders these cells hypersensitive to X rays, UV light, and hydroxyurea (14). More recently, UHRF1 has also been shown to facilitate the DNA damage response (DDR) to gamma irradiation (15,16). Consistently, DNA damage results in a decrease in the UHRF1 mRNA as well as protein level (1).…”
mentioning
confidence: 58%
“…UHRF1 depletion from cancer cells results in a variety of phenotypes, including cell cycle arrest (Li et al, 2011;Tien et al, 2011), apoptosis (Tien et al, 2011), loss of contact inhibition (Hopfner et al, 2002) and increased sensitivity to DNA-damaging agents (Arima et al, 2004;Mistry et al, 2010;Muto et al, 2002). Similar phenotypes have also been reported for DNMT1-deficient cells (Chen et al, 2007;Karpf and Matsui, 2005;Milutinovic et al, 2003;Unterberger et al, 2006;Vijayaraghavalu et al, 2013), suggesting DNA hypomethylation as the underlying cause of these phenotypes.…”
Section: Introductionsupporting
confidence: 50%
“…7,8,44,51,57,58 Thus, it was shown to be an important factor to facilitate DNA replication, cell cycle progression, transcriptional repression, and DNA damage response. 2,53,[59][60][61] This variety of functions argues for different states of the protein that provide distinct binding interfaces not only for histone and DNA modifications but also for specific protein interaction partners (Fig. 5).…”
mentioning
confidence: 99%